PENINGKATAN PRESTASI BELAJAR SISWA DALAM PEMBELAJARAN IPA MATERI BUNYI DENGAN MENERAPKAN METODE KOOPERATIF MODEL JIGSAW DI KELAS VIII A SMP NEGERI 2 - Dwi Retno Wahyuni (Florea : Jurnal Biologi dan Pembelajarannya, 2015)
This study aimed to increase student achievement in science learning material by applying sound Jigsaw model of cooperative methods in class VIIIA of SMP Negeri 2 Kwadungan school year 2013/2014 . Research using classroom action research ( PTK ) includes planning, action, observation, and reflection. The research instrument used syllabus, lesson plans, student activity sheets, observation sheets, and test. Data retrieval learning achievement tests and observations were performed every cycle . The results showed that students mastery of classical first cycle of 60 % , 87.5 % second cycle. show enthusiastic learn. Observations show their courage students to ask and answer questions discussion. The results showed that sound science learning material with the application of Jigsaw model of cooperative methods can improve student achievement .